2012
DOI: 10.1002/art.34315
|View full text |Cite
|
Sign up to set email alerts
|

Active involvement of alarmins S100A8 and S100A9 in the regulation of synovial activation and joint destruction during mouse and human osteoarthritis

Abstract: Objective. To investigate whether alarmins S100A8 and S100A9 are involved in mediating cartilage destruction during murine and human osteoarthritis (OA).Methods. Two different murine models of OA that differed in terms of synovial activation were compared. Cartilage destruction was measured histologically. Synovial biopsy and serum samples from OA patients were derived from the Cohort Hip and Cohort Knee (CHECK) patients with symptomatic early OA. Expression of mediators in the synovium was measured by reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
209
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(222 citation statements)
references
References 58 publications
(80 reference statements)
10
209
2
1
Order By: Relevance
“…42 A moderate CLP increase has been observed in the serum of OA patients compared with healthy controls, particularly in early OA. 37,57,113 Notably, in the study by Vogl et al…”
Section: Osteoarthritismentioning
confidence: 98%
See 2 more Smart Citations
“…42 A moderate CLP increase has been observed in the serum of OA patients compared with healthy controls, particularly in early OA. 37,57,113 Notably, in the study by Vogl et al…”
Section: Osteoarthritismentioning
confidence: 98%
“…24 Furthermore, in synovial biopsies from OA patients, levels of S100A8 and S100A9 correlated with markers of tissue damage, such as synovial lining thickness, sub-intima cellularity, and cartilage destruction. 57 Synovial CLP expression seems to be increased only if synovial inflammation is present. Vogl et al 57 demonstrated that in a murine model of collagenase-induced OA, which is characterized by synovial inflammation, the expression of S100A8 and S100A9 was higher compared with another model of OA, without synovial inflammation.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…and S100A9 are the inducers of MMPs (Moz et al 2016;Schelbergen et al 2012;van Lent et al 2012) (Figure 3) …”
mentioning
confidence: 99%
“…It is important to note that DMM only induces mild synovial infl ammation in mice [ 38 ], while enzymatically induced-OA model such as intra-articular injection of collagenase causes prolonged joint infl ammation [ 39 ]. Similar to OA in humans, wild type mice following DMM also show subchondral bone changes and osteophyte formation [ 33 , 36 , 40 ].…”
Section: Destabilization Of the Medialmentioning
confidence: 99%